2011
DOI: 10.1016/j.neurobiolaging.2009.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency reduces the benefits of progesterone treatment after brain injury in aged rats

Abstract: Administration of the neurosteroid progesterone (PROG) has been shown to be beneficial in a number of brain injury models and in two recent clinical trials. Given widespread vitamin D deficiency and increasing traumatic brain injuries (TBIs) in the elderly, we investigated the interaction of vitamin D deficiency and PROG with cortical contusion injury in aged rats. Vitamin D deficient (VitD-deficient) animals showed elevated inflammatory proteins (TNFα, IL-1β, IL-6, NFκB p65) in the brain even without injury. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
59
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 89 publications
4
59
0
Order By: Relevance
“…We are not the first to combine relevant combinations of treatments to administer following injury. There have been other instances of combination treatments showing benefit in the past, [64][65][66][67][68][69][70] including a combination of Prog and vitamin D. 64,65,68 In conclusion, we have demonstrated that a combination treatment of NAM and Prog provides improved neuroprotection and recovery of function in a variety of sensorimotor tasks, compared with NAM or Prog treatment alone. The current study provides a good initial assessment of the combination of NAM and Prog in a preclinical trial of controlled cortical impact of the sensorimotor cortex of the rat.…”
mentioning
confidence: 70%
“…We are not the first to combine relevant combinations of treatments to administer following injury. There have been other instances of combination treatments showing benefit in the past, [64][65][66][67][68][69][70] including a combination of Prog and vitamin D. 64,65,68 In conclusion, we have demonstrated that a combination treatment of NAM and Prog provides improved neuroprotection and recovery of function in a variety of sensorimotor tasks, compared with NAM or Prog treatment alone. The current study provides a good initial assessment of the combination of NAM and Prog in a preclinical trial of controlled cortical impact of the sensorimotor cortex of the rat.…”
mentioning
confidence: 70%
“…There is a report that the protective efficacy of P4 was significantly decreased in vit. D deficiency (Cekic et al, 2011), indicating that the neuroprotective function of P4 depends on vit. D availability.…”
Section: Potential Implications In Other Biological Processesmentioning
confidence: 99%
“…Vitamin D-deficient rats with traumatic brain injury show increased inflammation and greater open field test behavioural deficits in comparison with controls (Cekic et al, 2011). Although progesterone, a neurosteroid that has been beneficial as a treatment in traumatic brain injury in recent clinical trials (Wright et al, 2007;Xiao et al, 2008), was beneficial in injured control animals, there was no improvement with treatment in vitamin D-deficient animals.…”
Section: Vitamin D Deficiency and Traumatic Brain Injurymentioning
confidence: 99%
“…Vitamin D has been shown to downregulate the expression of inducible nitric oxide synthesis (iNOS) (Garcion et al, 1998) and to regulate the expression of gamma glutamyl transpeptidase (Garcion et al, 1999), an enzyme important in the glutathione pathway; these findings suggest that vitamin D has an important role in antioxidant metabolism. Vitamin D-deficient aged (22-month-old) male Fischer 344 rats have elevated inflammatory proteins in the brain, including TNFα and IL-6, indicating that baseline brain inflammation may be increased even without injury (Cekic et al, 2011). Furthermore, in middleaged (9-11-month-old) female Sprague-Dawley rats, a vitamin D-deficient diet produced elevated IL-6 levels within the brain and reduced insulin-like growth factor 1 (IGF-1) levels within plasma and brain following ischemia (Balden et al, 2012).…”
Section: Neuroprotectionmentioning
confidence: 99%
See 1 more Smart Citation